Evolving Business Strategies through Cyberpreneurship in the Age of AI and Automation - Maulana, Imam Ryan; Rahardja, Untung; Azizah, Nur; Rakhmansyah, Mohamad; Komara, Maulana Arif; Sebastian, Rizky (APTISI Transactions on Management (ATM), 2026)
The rapid advancement of Artificial Intelligence (AI) and automation has fundamentally transformed how organizations formulate and execute business strategies. As digital ecosystems continue to evolve, traditional approaches are no longer sufficient to maintain competitiveness, leading to the rise of cyberpreneurship as a strategic enabler for innovation and sustainability. The objective of this study is to examine how cyberpreneurship influences the evolution of business strategies through the adoption of AI and automation, focusing on strategic agility, innovation capability, and organizational adaptability. Using a quantitative research approach, data were collected from 250 digital entrepreneurs operating in creative and technology-based sectors. The data were analyzed using SmartPLS 4.0 to test the relationships among key constructs, including AI adoption, entrepreneurial innovation, business agility, and sustainable performance. The results indicate that AI adoption significantly enhances innovation capability, which mediates the relationship between cyberpreneurship and sustainable business performance. The findings highlight that businesses leveraging AI and automation can develop adaptive, data-driven, and customer-oriented strategies that strengthen long-term competitiveness. In conclusion, this study emphasizes that cyberpreneurship plays a crucial role in driving strategic transformation in the age of automation by fostering innovation and organizational resilience aligned with the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 12 (Responsible Consumption and Production).